Distribution of duricrusted bauxites and laterites on the Bamiléké plateau (West Cameroon): constraints from GIS mapping and geochemistry - Momo, M.N.; Yemefack, Martin; Tematio, P.; Beauvais, A.; Ambrosi, J. (Elsevier, 2016)
Estimation of the mineral resources potential is an important issue for most of developing countries. The spatial distribution of bauxites and lateritic land surfaces on the Bamiléké plateau (West Cameroon) has been investigated with a Boolean modeling process into a GIS environment on the basis of geological constraints such as elevation, rock and soil types, and landscape morphology. Field observation and SRTM (Shuttle Radar Topographic Mission) data allowed the differentiation of two lateritic land surfaces separated by a minimum altitude difference of about 60 m. These surfaces constrained by favorable rock types, slope steepness and soil types provided a potential lateritic bauxitic area of 381 km2 (17.2% of the total study site). Field validation and the integration of legacy spatial data resulted in an area of 60.1 km2 for potential bauxitic ores, i.e. obviously duricrusted bauxitic surfaces (with 47.8 km2 in the upper surface and 12.3 km2 in the lower surface). Alumina contents obtained from duricrust samples were analyzed by geostatistical methods and classical kriging interpolation to discriminate between bauxitic and ferruginous laterites. This highlighted a geochemical trend from higher alumina values on the upper surface (40–66 wt.%) to lower values on the lower surface (13–44 wt.%). Finally, our study documents two duricrusted lateritic surfaces arranged in a staircase manner and having different geochemical characteristics. The total bauxitic-rich surface is distributed in five spots throughout the study area and covers 56.2 km2, while ferruginous laterites occupy a spot of 3.9 km2. GIS mapping approach of lateritic land surfaces, accounting for reliable constraints, might be promising for larger scale investigations of mineral resources in Cameroon.